Modelling and simulation of DC chopper using MATLAB/Simulink / Maruan Ibrahim - Ibrahim, Maruan (2010)
A four Quadrant DC-to-DC converters used to control the DC motor drive that require forward and reverse motoring as well as forward and reverse braking, DC motor drive system controlled by Pulse Width Modulation (PWM) technique are expected to replace the conventional phase controlled system. This is due to their simple control, high ratability, low cost and fast response. A DC Chopper converts directly from DC-to-DC and also knows as DC-to-DC converter. It is considered a dc equivalent of an AC transformer with a continuously variable turn's ratio. DC Chopper may be classified according to the number of quadrant of the Vd-Id diagram and polarities in which there are capable of operating.